2016
DOI: 10.1038/ncomms12307
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic limits to gene regulation by global crosstalk

Abstract: Gene regulation relies on the specificity of transcription factor (TF)–DNA interactions. Limited specificity may lead to crosstalk: a regulatory state in which a gene is either incorrectly activated due to noncognate TF–DNA interactions or remains erroneously inactive. As each TF can have numerous interactions with noncognate cis-regulatory elements, crosstalk is inherently a global problem, yet has previously not been studied as such. We construct a theoretical framework to analyse the effects of global cross… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 72 publications
(137 reference statements)
4
74
0
Order By: Relevance
“…Thus, understanding the way the architecture of cis-regulatory elements determine gene expression behavior is pivotal not only to understand natural bacterial systems, but also to provide novel conceptual frameworks for the construction of synthetic promoters for biotechnological applications. Moreover, we were able to grasp, even in a narrow-scale subset of combinatorial diversities, biologically relevant effects of transcriptional crosstalk, a phenomenon that has been widely explored in eukaryotes, but overlooked in prokaryotes due to their significantly longer TF binding motifs with higher information-content (39, 40) -suggesting a predicted lower probability of crosstalk (41,42). Theoretical studies (41-48) have suggested important biological and evolutionary roles and tradeoffs for transcriptional crosstalk such as imposing intrinsic costs to cellular systems (41,42,44,46) -as gene expression might be improperly activated or repressed by non-cognate TFs at specific environmental contexts -, while also generating evolutionary flexibility that might be beneficial during the evolution of novel regulators through gene duplication (44).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, understanding the way the architecture of cis-regulatory elements determine gene expression behavior is pivotal not only to understand natural bacterial systems, but also to provide novel conceptual frameworks for the construction of synthetic promoters for biotechnological applications. Moreover, we were able to grasp, even in a narrow-scale subset of combinatorial diversities, biologically relevant effects of transcriptional crosstalk, a phenomenon that has been widely explored in eukaryotes, but overlooked in prokaryotes due to their significantly longer TF binding motifs with higher information-content (39, 40) -suggesting a predicted lower probability of crosstalk (41,42). Theoretical studies (41-48) have suggested important biological and evolutionary roles and tradeoffs for transcriptional crosstalk such as imposing intrinsic costs to cellular systems (41,42,44,46) -as gene expression might be improperly activated or repressed by non-cognate TFs at specific environmental contexts -, while also generating evolutionary flexibility that might be beneficial during the evolution of novel regulators through gene duplication (44).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we were able to grasp, even in a narrow-scale subset of combinatorial diversities, biologically relevant effects of transcriptional crosstalk, a phenomenon that has been widely explored in eukaryotes, but overlooked in prokaryotes due to their significantly longer TF binding motifs with higher information-content (39, 40) -suggesting a predicted lower probability of crosstalk (41,42). Theoretical studies (41-48) have suggested important biological and evolutionary roles and tradeoffs for transcriptional crosstalk such as imposing intrinsic costs to cellular systems (41,42,44,46) -as gene expression might be improperly activated or repressed by non-cognate TFs at specific environmental contexts -, while also generating evolutionary flexibility that might be beneficial during the evolution of novel regulators through gene duplication (44). Theoretical models have also been recently developed, suggesting the modulation of transcriptional crosstalk by different regulatory logic architectures (41,44), a phenomenon that could be experimentally supported in the present work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cooperativity was shown to be crucial for the highly dynamic dose‐response behavior of bceAB expression in the presence of increasing amounts of bacitracin, resulting in an accurate produce‐to‐demand strategy that adjusts cellular BceAB levels to just the right amount to cope with the current presence of bacitracin (Fritz et al ., ). These specific results on BceR cooperativity are in good agreement with a recent theoretical study, which identified cooperativity as an important mechanism to significantly reduce crosstalk in gene regulation (Friedlander et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, changes in regulatory networks are necessarily canalized by various internal and external factors. Internal factors include biophysical and structural constraints which have a number of effects, e.g., binding site programmability [50,53], buffering of noise in gene expression [92,93], regulatory crosstalk [94][95][96][97]85], gene susceptibility for accumulating mutations [98,99], evolvability [100], sensitivity to loss of interactions [101], genome architecture and chromosomal dynamics [102][103][104], etc. External factors include environmental conditions, thereby relating to various phenomena such as phenotypic plasticity [105][106][107], strength of selection [108,109], genetic drift [110], etc.…”
Section: Shared Edge Usage Even Amongst Highly Divergent Organismsmentioning
confidence: 99%